Exploring the Integration of Social-Emotional Learning in EFL Pre-Service Teacher Preparation in Morocco: A Mixed-Method Study - Mohammed Elmeski; Adil Bentahar (Anglica. An International Journal of English Studies)
Morocco’s educational policy documents underscore social-emotional competence as an important learning outcome. This study examines how the prominence of SEL in Morocco’s educational reform policy is reflected in the pre-service preparation of EFL teachers. The researchers have conducted a mixed-methods study that examines SEL integration in pre-service teacher preparation programs, and the extent to which student teachers report evidence of social-emotional learning associated with their pre-service preparation programs. Findings indicate that while two thirds of EFL student teachers reported that their pre-service preparation programs incorporate SEL skills aligned with the CASEL framework, responding to stress, managing anxiety and emotions, and collaboration stood out as areas requiring further strengthening in EFL teacher education programs in Morocco.